El temblor del héroe de Álvaro Pombo como ejemplo de filosofía líquida - Thierry Nallet (Cahiers de Civilisation Espagnole Contemporaine)
El temblor del héroe (Nadal Prize, 2012) is perhaps the most philosophical of Álvaro Pombo’s novels. It is a good example of, as Miguel de Unamuno called it, the «liquid philosophy» that can be found in contemporary Spanish literature. The novel examines the lives of characters who are part of a «liquid society» (Zygmunt Bauman) in which personal relations come apart and sink into a state of irresponsibility. This study argues that Pombo’s novel is to be considered as basically paradoxical.